A Multidisciplinary Approach to the Treatment of COVID-Associated Complications After Pancreatoduodenal Resection (Case Report) - T. E. Kim; D. A. Lebedev; M. M. Magomedbekov; K. A. Nugumanova; S. S. Petrikov; K. A. Popugayev; M. L. Rogal; P. A. Yartsev (Неотложная медицинская помощь, 2021)
We report a clinical case of treatment of a complicated postoperative course in a patient who underwent pancreatoduodenal resection associated with coronavirus infection. Prevention and treatment of such complications have been suggested.Pancreatoduodenal resection (PDR) is indicated for malignant tumors of the pancreatic head, duodenum or its large papilla, distal common bile duct, as well as in chronic pancreatitis with a predominant lesion of the pancreatic head with severe pain syndrome.The given clinical observation describes an example of treatment of a patient who developed a series of thromboembolic complications in the early stages after PDR performed for a neuroendocrine tumor of the pancreatic head. The oncology disease, extensive surgery such as PDR, and the postoperative period itself are risk factors for the development of various thromboembolic complications. According to the literature, the incidence of thromboembolic complications after PDR is 3–3.3%.The reason for the atypical course of the postoperative period when performing pancreatoduodenal resection in patients with tumor of the pancreas may be conditions that are not directly related to either the pathology of the pancreas or the features of the surgical intervention. When analyzing the patient’s condition, one should take into account the conditions of treatment. In such situations, proper detection of COVID-19 and adequate correction of therapy can fundamentally change the outcome of the disease.